Normal ADP-Induced Aggregation and Absence of Dissociation of the Membrane GP IIb-IIIa Complex of Intact Rat Platelets Pretreated with EDTA - Gachet, Christian; Stierlé, Anita; Ohlmann, Philippe; Lanza, François; Hanau, Daniel; Cazenave, Jean-Pierre (Thrombosis and Haemostasis, 1991)
ADP-induced platelet aggregation requires the presence of external calcium and fibrinogen. When human platelets are incubated for 30 min at 37° C with 5mM EDTA and then resuspended in a calcium containing medium, they lose their ability to bind fibrinogen and to aggregate in response to ADP stimulation. Under these conditions, the effect of EDTA is irreversible and accompanied by dissociation of the glycoprotein (GP) IIb-IIIa complex into its free subunits, GP IIb and GP IIIa. We studied the effect of incubation of intact rat platelets with 5 mM EDTA at 37° C from 30 to 120 min. EDTA treated rat platelets showed normal aggregation in response to 5 εM ADP in the presence of added purified rat fibrinogen and bound 125I-labeled rat fibrinogen at the same rate and magnitude after stimulation with 5 εM ADP as untreated platelets. Control and EDTA treated rat platelets, labeled or not with 125I and solubilized in Triton X-100, had a similar pattern of immunoprecipitates after crossed immunoelectrophoresis (CIE) analysis. The rat GP IIb-IIIa arc was located by incorporation of an 125I-labeled polyclonal anti-human GP IIb-IIIa antibody. In contrast, in experiments using rat platelet lysates, we demonstrated that the rat GP IIb-IIIa is a Ca2+-dependent heterodimer as it was dissociated by EDTA. Using SDS-PAGE and two-dimensional SDS-PAGE, the rat GP IIb-IIIa complex was found to have characteristics similar to the human complex with the exception that the light chain of the rat GP IIb was undetectable after 125I surface labeling. Small structural particularities of rat GP IIb-IIIa might still explain the functional differences observed between intact rat and human platelets treated with EDTA.